Wanita Bekerja: Antara Karier dan Keluarga - Lili Hidayati (Fakultas Ilmu Tarbiyah dan Keguruan, Institut Agama Islam Bakti Negara Tegal, 2022)
Women have a very important role in life both in the family and in the workplace. Women's participation in all walks of life cannot be denied. Women's skills and education require them to be able to appear in the public sphere. Working outside the home, a woman will experience a dual role that raises various implications that if not managed properly will make a woman commit acts of nusyuz which are prohibited in Islam. This research is a reflective-qualitative research on observations from several households that have been observed by the author. The result of this research is that when women know the signs of their feminine nature, they are able to work well and do not cause divisions in the family environment.